MHD Free Convective Flow along Vertical Oscillatory Plate with Radiative Heat Transfer in the Presence of Hall Current and Heat Source - Uday Singh Rajput; Mohammad Shareef (Institute for Research and Community Services (LPPM) ITB, 2019)
MHD free convective flow with oscillations of an infinite non-conducting vertical flat surface through a porous medium with Hall current in a rotating system was studied. The governing equations of the model were converted into dimensionless form. Analytical solutions for velocity and temperature were obtained with the help of the Laplace transform method. Graphs and tables are used in this paper to show the influence of various parameters on temperature, skin friction and velocity. It was observed that changes in plate oscillation, porous medium, radiation and Hall current have significant effects on fluid motion. Further, the skin friction near the surface is increased by the radiation parameter. The results obtained have large implications in the engineering and science fields.